Implementation of a comprehensive mathematical model for tilt-rotor real-time flight simulation - Barra, F.; Godio, S.; Guglieri, G.; Capone, P.; Monstein, R. (My University, 2019)
This paper aims at describing the effort performed by the joint research group of Politecnico di Torino and ZHAW (Zurich University of Applied Sciences) in achieving a novel implementation of a mathematical model for real-time flight simulation of tilt-rotors and tilt-wings aircraft. The focus is on the description of the current stage of the project, the achievements of the first version of the model, on-going improvements and future developments. The first part of the work describes the initial development of the overall simulation model: relying on several NASA reports on the Generic Tilt Rotor Simulator (GTRS), the mathematical model is revised and the rotor dynamic model is improved in order to enhance computational performance. In particular, the model uses the conventional mathematical formulation for non-dynamic inflow modelling based on Blade Element Momentum Theory. A novel but simple numerical method is used to ensure the convergence of the non-linear equation in every tested condition. The resulting simulation model and its development and implementation in the MATLAB/Simulink® environment is described. The second part of the work deals with the integration of the model in the ZHAW Research and Didactics Simulator (ReDSim), the replacement of the pilot controls by the introduction of a center stick and the corresponding adjustment of the force-feel system to suitable values for the tilt-rotor model. Subsequently, several pilot tests are carried out and preliminary feedbacks about the overall behaviour of the system are collected. Limits and weaknesses of the first release of the model are investigated and future necessary improvements are assessed, such as the development of a novel generic prop-rotor mathematical model. The third part introduces the novel multi-purpose rotor mathematical model which was developed to improve the overall tilt-rotor simulation model. The multi-purpose rotor model implements non-approximated flapping dynamics and inflow dynamic based on Pitt-Peters formulation. The validation of the nover rotor model is carried out with available data of both the XV-15 Research Aircraft and the UH-60 Helicopter.